Chip electrophoresis as a novel approach to measure the polyphenols reactivity toward human saliva. Issue 11 (3rd March 2014) - Rinaldi, Alessandra; Iturmendi, Néréa; Gambuti, Angelita; Jourdes, Michael; Teissedre, Pierre‐Louis; Moio, Luigi; Cifuentes, Alejandro
<x xml:space="preserve">Abstract</x> Saliva is a biological fluid with a multifunctional role that makes it interesting in terms of research and diagnostic possibilities. In food research, human saliva represented a useful tool by which we measure the tactile sensation elicited by polyphenol‐rich beverages called astringency. A method based on SDS‐PAGE analysis of saliva before and after the binding reaction with wine polyphenols has been successfully used in previous studies for measuring wine astringency by means of the saliva precipitation index. In this work, chip electrophoresis was used alternatively to SDS‐PAGE and results were compared. Chip electrophoresis provides a very good reproducibility for wine and grape astringency. Moreover, this approach is much faster than the conventional SDS‐PAGE method requiring several hours for an analysis. Another advantage over traditional gel is lower sample and reagent volume requirements, as well as the lower and less toxic wastes, contributing benefits to health and environment. The application of this novel method allowed, using the principal component analysis, to distinguish grapes and wines according to the saliva precipitation index and structural characteristics determined by the phoroglucinolysis analysis.